2014
DOI: 10.2105/ajph.2014.302097
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of a Community-Based Smoking Cessation Intervention in a Racially Diverse, Urban Smoker Cohort

Abstract: Objectives. We evaluated the feasibility, acceptability, and effectiveness, in addition to the effects of a psychoeducation-based orientation on smoking cessation knowledge for Courage to Quit (CTQ), an evidence-based smoking cessation intervention disseminated to racially diverse, urban community sites in Chicago, Illinois. Methods. Smokers (n = 1494; 55% African American) enrolled in 6-session full (n = 945) or 3-session short (n = 549) versions of CTQ in 2008 to 2012. Results. Orientation improved knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Various efforts have been put forward in the last decade to minimize racial disparities in cancer treatment and outcomes, including efforts by the NCI and both community-based and national smoking cessation programs geared towards minorities [32][33][34][35]. Increased emphasis on patient navigator programs by the NCI have been successful in improving timely access to quality care, but have not yet been implemented in lung cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…Various efforts have been put forward in the last decade to minimize racial disparities in cancer treatment and outcomes, including efforts by the NCI and both community-based and national smoking cessation programs geared towards minorities [32][33][34][35]. Increased emphasis on patient navigator programs by the NCI have been successful in improving timely access to quality care, but have not yet been implemented in lung cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown mixed results regarding gender as a determinant of successful cessation [9, 12, 20-24]. Numerous psychological factors have been associated with a positive response to treatment, including high baseline levels of self-efficacy [17, 18, 25-27], readiness and motivation to quit [16, 24, 28], low stress levels [29], low negative affect [30], no history of depression [31], and low anger [32]. Treatment-related factors include use of behavioral support [13, 33], adherence [34, 35], and absence of lapses during early treatment [36].…”
Section: Introductionmentioning
confidence: 99%
“…Targeted interventions geared toward minority communities are just starting. They are feasible and have shown good short‐term quit rates, but larger and longer studies are needed . One of the most effective ways to address smoking is through physician screening.…”
Section: Discussionmentioning
confidence: 99%
“…They are feasible and have shown good short-term quit rates, but larger and longer studies are needed. 26,27 One of the most effective ways to address smoking is through physician screening. Approximately 70% of smokers see a physician every year.…”
Section: Discussionmentioning
confidence: 99%